Taiwan's relations with mainland China [ a tail wagging two dogs - Su, Chi (Routledge contemporary Asia series ;, 2009)
Deals with the role of Taiwan's leadership politics in the development of Taiwan's mainland policy and the consequences for US-Taiwan relations